Decision-Making Process in Indonesia Immigration Policy During The Covid-19 Pandemic - Muhammad Sairi; Siti Yeni Aisyah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The COVID-19 pandemic has had a significant impact on various sectors of life, including immigration policy in Indonesia. This article aims to analyze the decision-making process in Indonesian immigration policy during the COVID-19 pandemic. Using a qualitative approach, this article examines policy documents and legislation, and conducts in-depth interviews with relevant policymakers. The results indicate that the immigration policy decision-making process during the pandemic was influenced by several factors, including: (1) pressure to prevent the spread of COVID-19, (2) the need to maintain economic stability, and (3) considerations of humanitarian aspects. In response to the pandemic, the Indonesian government has issued various dynamic and adaptive immigration policies. These policies include restrictions on the entry of foreign nationals, extensions of stay permits, and the repatriation of Indonesian citizens. While these policies have been successful in suppressing the number of COVID-19 cases, they have also presented several challenges, such as negative impacts on the tourism and investment sectors. This article concludes that the immigration policy decision-making process during the COVID-19 pandemic is complex and multidimensional. The government needs to continuously evaluate and improve existing immigration policies and strengthen coordination between relevant institutions in decision-making.